2006
DOI: 10.3114/sim.55.1.189
|View full text |Cite
|
Sign up to set email alerts
|

Species of Cercospora associated with grey leaf spot of maize

Abstract: Grey leaf spot is a serious yield-reducing disease of maize (Zea mays) in many parts of the world where this crop is cultivated. The causal organism associated with the disease is Cercospora zeae-maydis. Two potential sibling species have been recognized as Groups I and II. The DNA sequences for the internal transcribed spacers (ITS1 & ITS2), the 5.8S rRNA gene, elongation factor 1-α, histone H3, actin and calmodulin gene regions suggest that Groups I and II are two distinct species. Furthermore, Cercos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
91
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 9 publications
5
91
0
3
Order By: Relevance
“…Among the 91 isolates included in the U.S. study, only 12 were C. zeina isolates compared to 28 of the 69 Brazilian isolates. Nevertheless, the extent of genetic variability observed within and between Brazilian species supports the conclusions of Wang et al (1998) that the two groups they defined in the U.S. represent distinct gene pools and are likely to be different species, as suggested by Goodwin et al (2001) and recently confirmed by Crous et al (2006). This study also demonstrated a high genetic similarity among Brazilian, U.S., and African isolates.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…Among the 91 isolates included in the U.S. study, only 12 were C. zeina isolates compared to 28 of the 69 Brazilian isolates. Nevertheless, the extent of genetic variability observed within and between Brazilian species supports the conclusions of Wang et al (1998) that the two groups they defined in the U.S. represent distinct gene pools and are likely to be different species, as suggested by Goodwin et al (2001) and recently confirmed by Crous et al (2006). This study also demonstrated a high genetic similarity among Brazilian, U.S., and African isolates.…”
supporting
confidence: 69%
“…Similarly, the East African population of C. zeina was found to lack population structure and was indistinguishable from the U.S. C. zeina (group II) population based on AFLP and RFLP analyses (Okori et al, 2003). Thus, there appears to be limited genetic variability within populations of C. zeina worldwide, which is consistent with the likelihood that this species reproduces asexually and indicates that geographically separated populations do not differ substantially from the founding population, which is proposed to be in Africa (Dunkle and Levy, 2000;Crous et al 2006). …”
supporting
confidence: 63%
See 2 more Smart Citations
“…African and US group type II populations were co-specific with limited variability and type II species grew much slower and did not produce any toxins in culture. Crous et al (2006) and Meisel et al (2009) reclassified group type II as distinct species now called Cercospora zeina endemic in African countries. Okori et al (2003) confirmed the widespread presence of type II biotypes in East Africa (Kenya, Uganda, and Rwanda) and indicated that gene flow was high among African populations of C. zeaemaydis.…”
Section: Grey Leaf Spot Caused By Cercospora Zeae-maydismentioning
confidence: 99%